Simulation of Dispersal and Growth of Panulirus Ornatus Larvae in Coastal Ocean in Central Vietnam - Ngoc Anh, Giap; Cuong, Nguyen Kim; Duc Thinh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
This study analyzes the characteristics of wind, surface currents, temperature, salinity fields, and dispersal patterns of Panulirus Ornatus larvae in the Central coastal waters of Vietnam. The wind data were obtained from ERA5, while surface currents, temperature, and salinity were gathered from CMEMS, and the distribution of Panulirus Ornatus larvae was simulated using the OpenDrift model. El Niño and La Niña years were simulated and then compared with neutral years. The distribution results show that Panulirus Ornatus larvae tend to be dispersed northward during El Niño year, while during La Niña year, they were transported further offshore into the offshore area of the East Vietnam Sea. In neutral years, the larvae were predominantly dispersed northward, with a smaller portion drifting toward the offshore area, similar to the pattern observed during La Niña year. Additionally, the growth of the larvae was analyzed based on time and depth, revealing weight and size growth. These findings provide insights into the dispersal and growth of Panulirus Ornatus larvae. This information can inform sustainable management and exploitation of Panulirus Ornatus resources in Vietnam.